Long‐Term Increase in Antarctic Ice Sheet Vulnerability Driven by Bed Topography Evolution. Issue 20 (20th October 2020) - Paxman, Guy J. G.; Gasson, Edward G. W.; Jamieson, Stewart S. R.; Bentley, Michael J.; Ferraccioli, Fausto
Abstract: Ice sheet behavior is strongly influenced by the bed topography. However, the effect of the progressive temporal evolution of Antarctica's subglacial landscape on the sensitivity of the Antarctic Ice Sheet (AIS) to climatic and oceanic change has yet to be fully quantified. Here we investigate the evolving sensitivity of the AIS using a series of data‐constrained reconstructions of Antarctic paleotopography since glacial inception at the Eocene‐Oligocene transition. We use a numerical ice sheet model to subject the AIS to schematic climate and ocean warming experiments and find that bed topographic evolution causes a doubling in ice volume loss and equivalent global sea level rise. Glacial erosion is primarily responsible for enhanced ice sheet retreat via the development of increasingly low‐lying and reverse sloping beds over time, particularly within near‐coastal subglacial basins. We conclude that AIS sensitivity to climate and ocean forcing has been substantially amplified by long‐term landscape evolution. Plain Language Summary: The Antarctic Ice Sheet is situated above a large landmass, the geometry of which is an important control on the behavior of the ice sheet and how it responds to climatic change. However, Antarctica's subglacial landscape has evolved significantly since the formation of the first ice sheets approximately 34 million years ago, which implies that the sensitivity of the ice sheet to climate change may also have changed over time. Our ice sheet model experiments show that the progressive evolution of Antarctica's bed topography has enhanced the sensitivity of the Antarctic Ice Sheet to climate and ocean warming, meaning that a greater volume of ice is lost for a given warming scenario when using the modern topography compared to past topographies. In particular, the lowering of bed elevations by glacial erosion has caused a notable increase in ice sheet sensitivity within subglacial basins close to the ice sheet margin. Key Points: We investigate the influence of the progressive evolution of bed topography on the sensitivity of the Antarctic Ice Sheet to climatic change Bed topographic evolution since 34 Ma causes a doubling in Antarctic ice volume loss in our schematic ice sheet model experiments Antarctic Ice Sheet sensitivity to climate and ocean forcing has been substantially amplified by long‐term landscape evolution